2020
DOI: 10.20944/preprints202003.0466.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Disruption of SARS-CoV-2 RBD/ACE-2 Complex by Ubrogepant Is Mediated by Interface Hydration

Abstract: Background: COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global pandemic affecting approximately 490,000 people and accounting for more than 22,000 deaths and has no generally cure. Here, the recently resolved 3D structure of SARS-CoV-2 receptor binding domain (RBD) in complex with its receptor-the angiotensin converting enzyme-2 (ACE-2) have provided the basis for screening chemical database for novel entry inhibitors. Methods: Molecular docking protocols have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Therefore, leading to a binding and cellular receptor recognition unattainable. Therefore, UBR exhibits a novel therapeutic candidate in combating SARS‐CoV‐2 since it binds to proportionally high affinity with free RBD, ACE‐2 receptor, and SARS‐CoV‐2 RBD/ACE‐2 complex based on only binding affinity calculations (Omotuyi et al, 2020 ). The other studies in this area are demonstrated in Table 2 .…”
Section: Computational Drug Discovery Approaches For Covid‐19mentioning
confidence: 99%
“…Therefore, leading to a binding and cellular receptor recognition unattainable. Therefore, UBR exhibits a novel therapeutic candidate in combating SARS‐CoV‐2 since it binds to proportionally high affinity with free RBD, ACE‐2 receptor, and SARS‐CoV‐2 RBD/ACE‐2 complex based on only binding affinity calculations (Omotuyi et al, 2020 ). The other studies in this area are demonstrated in Table 2 .…”
Section: Computational Drug Discovery Approaches For Covid‐19mentioning
confidence: 99%